2021
DOI: 10.21037/atm-21-6243
|View full text |Cite
|
Sign up to set email alerts
|

The enlargement rate of ventricular septal rupture is a risk factor for 30-day mortality in patients with delayed surgery

Abstract: Background: Postinfarction ventricular septal rupture (VSR) is an uncommon but challenging mechanical complication for surgeons. This study analyzed the impacts of rupture size on surgical outcomes in patients with VSR.Methods: During a 15-year period, from January 2006 to December 2020, 112 patients underwent repairs of postinfarction VSR. Patient clinical data, including angiographic and echocardiographic findings, operative procedures, early morbidity and mortality, and survival time were collated. Univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In this study, the survival rate of patients who underwent repair after 2 weeks of septal perforation was greatly improved, including those who used a mechanical circulatory support to extend the timing of surgery beyond 2 weeks ( P < 0.05). Our study showed that women, worse Killip classification and cardiogenic shock were risk factors for long-term mortality in VSR patients, which is consistent with many existing studies ( 3 , 35 , 36 ). However, due to differences in the study cohort, age did not have a significant effect on survival in patients with VSR in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the survival rate of patients who underwent repair after 2 weeks of septal perforation was greatly improved, including those who used a mechanical circulatory support to extend the timing of surgery beyond 2 weeks ( P < 0.05). Our study showed that women, worse Killip classification and cardiogenic shock were risk factors for long-term mortality in VSR patients, which is consistent with many existing studies ( 3 , 35 , 36 ). However, due to differences in the study cohort, age did not have a significant effect on survival in patients with VSR in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The 2013 AHA guidelines for STEMI recommended emergency surgical repair for all patients with VSR, even in hemodynamically stable patients ( 11 ). However, due to an inadequate transportation system in middle-income economies like China, a large proportion of VSR patients cannot receive emergency surgery in a timely manner and therefore, unplanned delayed surgery is common in China ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation